Analysis of Internationalization Strategies of German Electricity Companies - Nosek, Niklas; Jaklová, Martina L.; Hnilica, Jiří, 1976-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The thesis analyzes internationalization strategies and processes that were used by major German electricity companies during their transition from purely national companies to some of the world's largest electricity corporations with operations in many different countries. The paper starts out by outlining theoretical elements that are available to companies in general and then provides an in-depth analysis of the internationalization that Germany's major Electricity companies went through after the liberalization of German and European electricity markets. Based on this, the thesis then identifies key internationalization patterns in the German electricity industry and, by taking into account future developments, provides factors that will influence further internationalization strategies in the segment.
Vedoucí práce: Martina L. Jaklová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses